Implikasi Teologi Kovenan terhadap Keutamaan Yesus dalam Kehidupan Jemaat: Perspektif Ibrani 7:22 - Purwonugroho, Daniel Pesah; Latunussa, Reinhart Helbert Albrow (Sekolah Tinggi Teologi Baptis, Jakarta, 2024)
This article aims to explore the relationship between covenant theology and the supremacy of Jesus from the perspective of Hebrews 7:22, as well as its implications for the congregation's life. Covenant theology describes the relationship between God and humanity as recorded in the Bible, from Genesis to Revelation. It articulates God's promises to humanity, including the promise of salvation. The Book of Hebrews is a text that contains both covenant theology and high Christology. The supremacy of Jesus is also described in Hebrews. Hebrews 7:22 is a verse that explains the intersection between covenant theology and the supremacy of Jesus. Understanding covenant theology can lead the congregation to reverence and awe toward a God who interacts directly with humanity. The supremacy of Jesus plays a central role as the fulfiller and guarantor of the new covenant for humanity through His redemptive work. Using a qualitative descriptive approach, this study will expose the implications of covenant theology for the supremacy of Jesus from the perspective of Hebrews 7:22. AbstrakArtikel ini dibuat untuk menjelajahi hubungan teologi kovenan terhadap keutamaan Yesus dalam persepktif Ibrani 7:22 serta implikasinya bagi kehidupan jemaat. Teologi kovenan melukiskan hubungan antara Allah dan manusia yang terdapat di dalam catatan Alkitab dari Kejadian sampai dengan Wahyu. Teologi kovenan mengartikulasikan janji Allah kepada manusia termasuk janji keselamatan. Kitab Ibrani adalah termasuk kitab yang mengandung teologi kovenan dan juga kristologi yang tinggi. Keutamaan Yesus juga dideskripsikan di dalam kitab Ibrani. Ibrani 7:22 adalah ayat yang menjelaskan persinggungan antara teologi kovenan serta keutamaan Yesus. Pengenalan teologi kovenan akan membawa jemaat mengalami rasa hormat dan takjub tentang Allah yang berinteraksi secara langsung kepada umat manusia. Keutamaan Yesus memiliki peranan sentral sebagai pemenuh dan penjamin kovenan baru bagi manusia melalui karya penebusanNya. Dengan penelitian kualitatif deskriptif, penelitian ini akan mengekspos implikasi teologi kovenan terhadap keutamaan Yesus dalam sudut pandang Ibrani 7:22.